Coronary Calcium Scoring and Modifiable Coronary Risk Factors - Sharma, Lucky; Karki, Dambar Bahadur; Shahi, Aanchal; Sharma, Dikshya (Journal of Lumbini Medical College, 2017)
Introduction: Non-invasive coronary calcium scoring predicts earliest atherosclerotic changes in the coronary arteries on the basis of amount of calcium deposited in the coronary arteries. This study was done to analyze calcium scores in patients with different risk factors for coronary artery disease (CAD). Methods: This was a cross sectional study conducted from 1st November 2015 to 30th April 2016 at Kathmandu Medical College Teaching Hospital. Patient with cardiovascular risk factors were included in the study. These patients underwent coronary calcium scoring. Calcium scores were then compared with the presence of risk factors. Results: Total 467 participants were included in the study. There were 309 (62.2%) males and 158 (33.8%) females. Mean age of patient was 56.6 year (SD = 12.7). The difference in the scores observed with presence or absence of risk factors were statistically significant for gender, smoking, and hypertriglyceridemia (p<0.05) but not significant for impaired fasting glucose, hypertension, and body mass index. Conclusion: This study suggested that presence of traditional risk factors does not necessarily indicate high coronary calcium level.